Community pharmacists' evolving role in Canadian primary health care: a vision of harmonization in a patchwork system - Taylor Raiche; Robert Pammett; Shelita Dattani; Lisa Dolovich; Kevin Hamilton; Natalie Kennie-Kaulbach; Lisa McCarthy; Derek Jorgenson (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Canada's universal public health care system provides physician, diagnostic, and hospital services at no cost to all Canadians, accounting for approximately 70% of the 264 billion CAD spent in health expenditure yearly. Pharmacy-related services, including prescription drugs, however, are not universally publicly insured. Although this system underpins the Canadian identity, primary health care reform has long been desired by Canadians wanting better access to high quality, effective, patient-centred, and safe primary care services. A nationally coordinated approach to remodel the primary health care system was incited at the turn of the 21st century yet, twenty years later, evidence of widespread meaningful improvement remains underwhelming. As a provincial/territorial responsibility, the organization and provision of primary care remains discordant across the country. Canadian pharmacists are, now more than ever, poised and primed to provide care integrated with the rest of the primary health care system. However, the self-regulation of the profession of pharmacy is also a provincial/territorial mandate, making progress toward integration of pharmacists into the primary care system incongruent across jurisdictions. Among 11,000 pharmacies, Canada's 28,000 community pharmacists possess varying authority to prescribe, administer, and monitor drug therapies as an extension to their traditional dispensing role. Expanded professional services offered at most community pharmacies include medication reviews, minor/common ailment management, pharmacist prescribing for existing prescriptions, smoking cessation counselling, and administration of injectable drugs and vaccinations. Barriers to widely offering these services include uncertainties around remuneration, perceived skepticism from other providers about pharmacists' skills, and slow digital modernization including limited access by pharmacists to patient health records held by other professionals. Each province/territory enables pharmacists to offer these services under specific legislation, practice standards, and remuneration models unique to their jurisdiction. There is also a small, but growing, number of pharmacists across the country working within interdisciplinary primary care teams. To achieve meaningful, consistent, and seamless integration into the interdisciplinary model of Canadian primary health care reform, pharmacy advocacy groups across the country must coordinate and collaborate on a harmonized vision for innovation in primary care integration, and move toward implementing that vision with ongoing collaboration on primary health care initiatives, strategic plans, and policies. Canadians deserve to receive timely, equitable, and safe interdisciplinary care within a coordinated primary health care system, including from their pharmacy team.